The therapeutic relationship in Cognitive Behaviour Therapy with depressed adolescents: A qualitative study of good‐outcome cases. (22nd May 2019) - Wilmots, Eva; Midgley, Nick; Thackeray, Lisa; Reynolds, Shirley; Loades, Maria
Abstract : Objectives: This paper aimed to explore client experiences of the therapeutic relationship among adolescents with good outcomes after receiving Cognitive Behaviour Therapy (CBT) for moderate to severe depression. Design: This was a qualitative study employing Interpretative Phenomenological Analysis (IPA). Methods: As part of a randomized clinical trial, 77 adolescents with moderate to severe depression were interviewed using a semi‐structured interview, which was audio‐recorded. Five of these interviews, with adolescents aged 14–18 years who completed CBT and had good outcomes, were purposively sampled and analysed using IPA. Results: The findings indicated that a positive therapeutic relationship was fostered with therapists who respected the adolescents' autonomy and sense of individuality, while offering experiences of emotional closeness and connection. This was achieved by balancing the dual roles of being 'friendly' and affable, with being a 'professional expert' thereby embodying a collaborative and egalitarian approach. Conclusions: The therapeutic relationship in CBT can help to motivate adolescents to engage with cognitively and emotionally challenging tasks. By providing an understanding of what helps and hinders the development of a positive therapeutic relationship, the current findings offer important insight into how therapists can foster positive relationships with depressed adolescents. This knowledge will make it more likely that adolescents will engage in the treatment process and in turn experience greater therapeutic gains. Practitioner points: Offers a detailed phenomenological analysis of what fostered a positive therapeutic relationship in good outcome CBT, and what was experienced as harmful from the adolescents' perspective. Provides support that the therapeutic relationship is crucial in CBT; a respectful and understanding relationship provides a platform for the adolescent to carry out CBT activities and tasks.